(untitled) (Ustozlar uchun, 2024)
Abstract. Along the food chain, radionuclides enter the human body, accumulate, have a negative effect, have a radiotoxicological effect. Such interest in the effects of radioactive substances arose due to the harmful effects of strontium-90 (Sr-90) and cesium-137 (Cs-137) on the body.